Toward spatial fit in the governance of global commodity flows - Coenen, Johanna; Sonderegger, Gabi; Newig, Jens; Meyfroidt, Patrick; Challies, Edward; Bager, Simon L.; Busck-Lumholt, Louise M.; Corbera, Esteve; Friis, Cecilie; Frohn Pedersen, Anna; Laroche, Perrine C.S.J.; Paitan, Claudia Parra; et al. (Ecology and Society, 2023)
Global commodity flows between distally connected social-ecological systems pose important challenges to sustainability governance. These challenges are partly due to difficulties in designing and implementing governance institutions that fit or match the scale of the environmental and social problems generated in such telecoupled systems. We focus on the spatial dimension of governance fit in relation to global commodity flows and telecoupled systems. Specifically, we draw on examples from land use and global agricultural commodity governance to examine two overarching types of governance mismatches: boundary mismatches and resolution mismatches. We argue that one way to address mismatches is through governance rescaling and illustrate this approach with reference to examples of three broad types of governance approaches: trade agreements, due diligence laws, and landscape approaches to supply chain governance. No single governance approach is likely to address all mismatches, highlighting the need to align multiple governance approaches to govern telecoupled systems effectively.
Created from Fastlane, Scopus look-up
Keywords: environmental governance; human-environment interactions; scale; spatial mismatch; supply chain; telecoupling